Caracterización de residuos sólidos urbanos del cantón Santiago de Quero, provincia de Tungurahua - Medrano Allauca, Juan Carlos (2025)
This study characterized urban residential solid waste in Santiago de Quero canton, Tungurahua province, using a quantitative methodology that included sampling in 55 homes over eight consecutive days. The results identified a bipolar socioeconomic structure, with a predominance of stratum B (72,86%) and C (27,14%), and an urban population of 3269 inhabitants. The weighted per capita production (PPC) was 0,372 kg/inhabitant/day, showing a significant weekly variation, with a peak on Sundays (0,397 kg/inhabitant/day) and a minimum on Wednesdays (0,326 kg/inhabitant/day), with no statistically significant differences between strata. The physical composition was dominated by organic waste (80,6%), while recyclables accounted for only 11,5%. The weighted density was 215,78 kg/m³, with a notable difference between stratum B (236,27 kg/m³) and C (160,78 kg/m³). These findings highlight the need to implement differentiated management systems, with an emphasis on the recovery of organic matter, optimizing collection routes based on density and weekly variability, and strengthening environmental education. The research provides a fundamental technical basis for planning an efficient waste management system adapted to local conditions and can serve as a replicable model in cantons with similar socioeconomic characteristics.